2010
DOI: 10.1063/1.3319509
|View full text |Cite
|
Sign up to set email alerts
|

Effects of side-chain packing on the formation of secondary structures in protein folding

Abstract: We have recently shown that protein folding is driven by the water-entropy gain. When the alpha-helix or beta-sheet is formed, the excluded volumes generated by the backbone and side chains overlap, leading to an increase in the total volume available to the translational displacement of water molecules. Primarily by this effect, the water entropy becomes higher. At the same time, the dehydration penalty (i.e., the break of hydrogen bonds with water molecules) is compensated by the formation of intramolecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
62
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 64 publications
(144 reference statements)
1
62
1
Order By: Relevance
“…3c), the decrease in the total excluded volume is quite large. Protein folding can be characterized by the formation of as much α-helix and β-sheet as possible and the close packing of the backbone and side chains with a variety of geometric features (Yasuda et al 2010). Using a tube model mimicking the backbone or its portion, some other groups (Snir and Kamien 2007;Hansen-Goos et al 2007;Poletto et al 2008) have examined which of the α-helix and the β-sheet is more stabilized when the density and molecular diameter of the solvent are varied as important parameters.…”
Section: Thermodynamics Of Apoplastocyanin Foldingmentioning
confidence: 99%
“…3c), the decrease in the total excluded volume is quite large. Protein folding can be characterized by the formation of as much α-helix and β-sheet as possible and the close packing of the backbone and side chains with a variety of geometric features (Yasuda et al 2010). Using a tube model mimicking the backbone or its portion, some other groups (Snir and Kamien 2007;Hansen-Goos et al 2007;Poletto et al 2008) have examined which of the α-helix and the β-sheet is more stabilized when the density and molecular diameter of the solvent are varied as important parameters.…”
Section: Thermodynamics Of Apoplastocyanin Foldingmentioning
confidence: 99%
“…[1][2][3][4] This is mostly due to its pivotal importance in nanotechnologies 5,6 and in protein interactions understood in the broadest sense. 7 The understanding and manipulation of such interfaces require a multiscale approach to water dielectrics, an unsettled matter at this time.…”
mentioning
confidence: 99%
“…Recent theoretical studies based on the statistical thermodynamics of fluids have shown that the translational entropy of water is a principal driving force in a variety of biological self-assembly processes such as protein folding [23][24][25][26][27][28], molecular recognition between guest ligands and host enzymes [27,29,30], and aggregation of protein molecules like the amyloid fibril [27,31,32]. We first note that the presence of proteins generate an excluded volume (EV) which the centers of water molecules cannot enter [23,24].…”
Section: Introductionmentioning
confidence: 99%